2022
DOI: 10.1155/2022/2141882
|View full text |Cite|
|
Sign up to set email alerts
|

Network Pharmacology and Molecular Docking-Based Investigation of Potential Targets of Astragalus membranaceus and Angelica sinensis Compound Acting on Spinal Cord Injury

Abstract: Background Astragalus membranaceus (Huang-qi, AM) and Angelica sinensis (Dang-gui, AS) are common Chinese herbal medicines and have historically been used in spinal cord injury (SCI) therapies. However, the underlying molecular mechanisms of AM&AS remain little understood. The purpose of this research was to explore the bioactive components and the mechanisms of AM&AS in treating SCI according to network pharmacology and the molecular docking approach. Methods AM&AS act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“… Rhizoma chuanxiong (RC) [ 39 , 42 ] Alkaloid Tetra-methylpyrazine , Ferulic acid, senkyunolide I, dan ligustilide Apoptosis, inflammation Increases BCL-2, decreases Caspase-3, activation of the P13K/AKT pathway, interacting with the ALB, AKT1, MAPK1, MMP9, and EGFR genes decreases proinflammatory cytokines (IL-1mit and TNF-α) and increases IL-10). Angelicae sinensis radix (ASR) [ 15 , 50 ] Polysaccharides, Z-Stillicide, dan ferulic acid Apoptosis, inflammation, regenerative Activation of the P13K/AKT pathway, inhibits the NF-κB path, lowering MPO, helping the differentiation of stem cells. Carthamus tinctorius (SY) [ 9 , 40 , 51 ] Safflower Yellow Apoptosis, myelin regeneration Increasing BCL-2, lowering Bax and Caspase-3, triggers growth and expansion of neurit through the activation of the BDNF/TrkB/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Rhizoma chuanxiong (RC) [ 39 , 42 ] Alkaloid Tetra-methylpyrazine , Ferulic acid, senkyunolide I, dan ligustilide Apoptosis, inflammation Increases BCL-2, decreases Caspase-3, activation of the P13K/AKT pathway, interacting with the ALB, AKT1, MAPK1, MMP9, and EGFR genes decreases proinflammatory cytokines (IL-1mit and TNF-α) and increases IL-10). Angelicae sinensis radix (ASR) [ 15 , 50 ] Polysaccharides, Z-Stillicide, dan ferulic acid Apoptosis, inflammation, regenerative Activation of the P13K/AKT pathway, inhibits the NF-κB path, lowering MPO, helping the differentiation of stem cells. Carthamus tinctorius (SY) [ 9 , 40 , 51 ] Safflower Yellow Apoptosis, myelin regeneration Increasing BCL-2, lowering Bax and Caspase-3, triggers growth and expansion of neurit through the activation of the BDNF/TrkB/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moleac (MLC) 901 is an enhanced phytopharmaceutical that represents an advancement over its predecessor, MLC601 (also known as Danqi Piantang Jiaonang/DPJ ). Research indicates that MLC901, which consists of a blend of active components, comprises crucial compounds that can generate favorable conditions for the growth and specialization of progenitor cells [ 15 ]. The extensive utility of MLC901 administration in facilitating stroke rehabilitation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…System analytic methodologies, such as network pharmacology, are promising for developing fresh approaches to elucidating the drug-gene-disease relationship [ 24 ]. The network pharmacology approach of TCM presents a novel study methodology [ 25 ]. This strategy will promote the use of evidence-based medicine in TCM, helping to prove MG's therapeutic value and improving the current drug discovery process [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%